Tradisi Mambere Tungkot Pakon Duda-Duda Bani Orang Tua Sebagai Wujud Penghormatan Dalam Masyarakat di Desa Sipoldas Kab Simalungun - Sinaga, Ummi Hayati; Dora, Nuriza (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research examines the habits of the Simulungun Batak community in the mambere tungkot pakon duda – duda tradition as a form of respect for parents (saur matua). This research aims to explore understanding, preserving and respecting cultural heritage and the values contained therein. The research method used is qualitative, which includes participant observation, interviews with local community members, and analysis of aspects of the ceremony, symbolism, and cultural values involved in this tradition. The results of the research show that the Mambere Tungkot Pakon Duda-Duda tradition is a form of expression of respect and gratitude from children to their parents. This tradition involves various symbols, such as betel leaves, sticks, and typical Batak dishes, which reflect cultural meanings and values. The values reflected in this tradition include aspects of theory, economics, religion, art, solidarity and power. Efforts to preserve and revitalize this tradition involve collaboration with local communities, education of the younger generation, and participation in cultural festivals as steps to maintain and revive this tradition.